Autism under the umbrella of ESSENCE - Fernell, Elisabeth; Gillberg, Christopher (Frontiers in Psychiatry, 2023)
This brief article gives a short overview of “comorbidity” in autism. The most common co-occurring disorders will be presented and discussed within the context of ESSENCE (Early Symptomatic Syndromes Eliciting Neurodevelopmental Clinical Examinations), a concept that provides a holistic perspective for neurodevelopmental disorders. The ESSENCE concept also considers the heterogeneous and changing clinical panorama of developmental disorders over time, and also the multifactorial etiologies, including so called behavioral phenotype syndromes. Aspects on behavioral interventions in autism are presented - interventions that need to be adapted and take into account all non-autism associated ESSENCE, including intellectual disability and ADHD. The article also focuses on current research on pharmacological intervention based on the hypothesis of imbalance in excitatory/inhibitory transmitter systems in autism and some other ESSENCE.